2021
DOI: 10.1155/2021/6648611
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of the Effect of Health Management of Chronic Diseases and Metabolic Disorders under the Guidance of B-Ultrasound

Abstract: Chronic diseases are diseases with insidious onset, prolonged duration, and intractability and are associated with complex etiology and multiple morbidities, including hypertension, obesity, liver disease, kidney disease, cancer, cardiovascular disease, and chronic lung disease. For patients with chronic diseases, although the cause of the disease is not in the spleen and stomach, medication or further development of the disease will affect the function of the spleen and stomach disorders, leading to worsening… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In recent years, humans started giving more importance to their health, especially due to the outbreak of various kinds of disorders and constant deterioration in their health [ 15 ]. Consequently, they ate fresh fruits and vegetables and other kinds of green leafy vegetables as part of their daily diet to ensure adequate nutrition.…”
Section: Sprouts Vs Microgreens Vs Baby Greens Vs Mature Plantsmentioning
confidence: 99%
“…In recent years, humans started giving more importance to their health, especially due to the outbreak of various kinds of disorders and constant deterioration in their health [ 15 ]. Consequently, they ate fresh fruits and vegetables and other kinds of green leafy vegetables as part of their daily diet to ensure adequate nutrition.…”
Section: Sprouts Vs Microgreens Vs Baby Greens Vs Mature Plantsmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%